PENGARUH MEDIA SIMULASI KOMPUTER TERHADAP HASIL BELAJAR MAHASISWA PADA MATERI KINEMATIKAGERAK - Angraeni, Lia; Puspitasari, Henny (Universitas Tanjungpura, 2019)
AbstractThe purpose of this study was to determine the effect of using computer simulation media on learning outcomes of Physics in IKIP PGRI Pontianak ICT Education students. The population of this study is the 1st semester ICT Education students consisting of 2 classes totaling 79 students. Determination of the sample using Cluster Random Sampling technique, the sample used in this study is 1 class, namely class A Morning. The research method used is the experimental method. Learning outcomes data were taken using cognitive test instruments using multiple choice tests. The results showed that the average student learning outcomes before applied learning using simulation media amounted to 49.32 with a standard deviation of 14.45 and the average student learning outcomes after applied learning using simulation media amounted to 81.28 with a standard deviation of 14.63 . From the results of the analysis using the Wilcoxon Match Pairs test, Zhitung is 1,009 which is smaller than Zttable which is equal to 1,645. Then H0 is rejected and Ha is accepted, meaning that there are differences in student learning outcomes before and after being given learning using simulation media on the material of motion kinematics. Thus, the use of computer simulation media on the material of motion kinematics can improve student learning outcomes.Keywords: Computer simulation media, motionÂ kinematics.Â